Neoliberal and conservative trends for families and drugs - Araújo, Evelly Nathália Lira de; Vieira, Ana Cristina de Souza (Argumentum, 2024)
This study critically analyses the political-ideological position of the Bolsonaro mandate regarding the relationship between the State, the family and drug users. It is based on the content of the booklet How to help a drug-dependent person, published in 2020. The article is based on historical-dialectical materialism; it understands that neoliberalism and conservatism have imprinted their mark on the pedagogy of the booklet. The analysis also considers the principles of Psychiatric Reform and Harm Reduction. The results indicate that the neoliberal and conservative configuration of that Far-Right government revolved around its lack of responsibility for the treatment and care of users of alcohol and other drugs, the compulsory accountability of family members, and the undemocratic conduct of the principles of Psychiatric Reform and Harm Reduction.